A reading of power relations in the transformation of urban planning in the municipalities of the Greater Pretoria region (now Tshwane) : 1992-2002 - Oranje, Mark (University of Pretoria, 2013)
Thesis (DPhil (Town and Regional Planning))--University of Pretoria, 2006.